(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Santi TD, Siregar TN, Sutriana A, Andini R, Candra A. 2022. Phytochemical test and optimization of transdermal patches of Carica papaya extract: Formulation design of transdermal patch as candidate drug for wound healing. Biodiversitas 23: 2904-2913. Papaya leaves contain metabolite compounds thathave anti-inflammatory and wound-healing properties. This leaf extract as a transdermal patch allows easy application for wound healing. This study aimed to examine the phytochemicals of papaya leaves and determine the formulation of the transdermal patch. This study employed qualitative methods with color testing and quantitative methods with Gas Chromatography-Mass Spectrophotometry (GC-MS) to determine the phytochemical profiles of papaya leaves. The optimization test of patches used Response Surface Methodology with Box-Behnken design on Expert Version 12 software. There were three factors (x) tested in the study, namely PVP, ethyl cellulose, and Ethanol Extract of Papaya Leaves (EECP). There were also three responses (y) investigated, namely thickness, weight, and moisture content. The phytochemical color testingresults revealed the presence of alkaloids, steroid, terpenoid, saponins, flavonoids, phenolic compounds and the GC-MS analysis showed six compounds with the widest areas. From an ANOVA analysist, the p-value was significant (<0.5) while the match value was less significant (p-value >5%). The optimal patch found in this study was the one containing PVP (0.3 mg), ethyl cellulose (0.4 mg), and EECP (0.3 mg). In terms of response values (y), the patch had a ??thickness of 0.25 mm, a weight of 82 mg, and a moisture content of 4.39%.